2014
DOI: 10.1108/ijwhm-03-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Are incremental changes in physical activity and sedentary behaviours associated with improved employee health?

Abstract: Abstract:OBJECTIVES: Explore the impact of incremental increases in physical activity and incremental decreases in sedentary behaviours on health outcomes in employees of five organisations. Investigate the association between physical activity and sedentary behaviours.METHODS: Self-reported physical activity and sedentary behaviours were recorded at four time points (baseline, 3, 6, 12 months). BMI, % body fat, waist circumference, blood pressure and resting heart rate were collected in health checks (baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Tables and S5 provides a summary of the evidence including total, weekday‐specific and weekend‐specific sitting time. A total of 69 studies reported on at least one correlate (unpublished results: Al‐Hazzaa, Barbieri, Baron, Carrington, Conroy, De Cocker, Freak‐Poli, Leicht, Lin, Saidj and Vaidya). Importantly, differences in direction of association across correlates often occurred between weekdays versus weekend versus total weekly sitting time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables and S5 provides a summary of the evidence including total, weekday‐specific and weekend‐specific sitting time. A total of 69 studies reported on at least one correlate (unpublished results: Al‐Hazzaa, Barbieri, Baron, Carrington, Conroy, De Cocker, Freak‐Poli, Leicht, Lin, Saidj and Vaidya). Importantly, differences in direction of association across correlates often occurred between weekdays versus weekend versus total weekly sitting time.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence also consistently showed a lack of association between education and transportation SB; marital status and leisure and transportation SB; area SES and transportation SB; social support and leisure SB, sitting and total ST; and finally, crime/safety and leisure, sitting and total SB. All of the experimental evidence examined changes in the office/work environment . Very few trends in sex differences were noted, but several individual studies reported differences in direction of associations between men and women .…”
Section: Resultsmentioning
confidence: 99%
“…Use of these criteria allow researchers to look beyond the BCW and explore feasibility issues before trialling an intervention. Using the BCW to design interventions is becoming more common, and it has been successfully used to understand behaviour change in different contexts, such as sexual counselling [48], medication management [49, 50], auditory rehabilitation [51], and physical activity [52]. Development of interventions using the full BCW to reduce workplace sitting however, is limited, with only the Stand More AT Work (SMArT) study found to target hospital office workers [53].…”
Section: Theoretical Framework Underpinning the Intervention Designmentioning
confidence: 99%
“…Use of these criteria allow researchers to look beyond the BCW and explore feasibility issues before trialling an intervention. Using the BCW to design interventions is becoming more common, and it has been successfully used to understand behaviour change in different contexts, such as sexual counselling [48], medication management [49,50], auditory rehabilitation [51], and physical activity [52]. Development of interventions using the full BCW to reduce workplace sitting however, is limited, with only the Stand More AT Work (SMArT) study found to target hospital office workers [53].…”
Section: Theoretical Framework Underpinning the Intervention Designmentioning
confidence: 99%